2019
DOI: 10.1016/j.jtho.2018.12.020
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Based versus RNA-Based Detection of MET Exon 14 Skipping Events in Lung Cancer

Abstract: Introduction: Genomic variants that lead to MET proto-oncogenem receptor tyrosine kinase (MET) exon 14 skipping represent a potential targetable molecular abnormality in NSCLC. Consequently, reliable molecular diagnostic approaches that detect these variants are vital for patient care.Methods: We screened tumor samples from patients with NSCLC for MET exon 14 skipping by using two distinct approaches: a DNA-based next-generation sequencing assay that uses an amplicon-mediated target enrichment and an RNA-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 13 publications
4
125
0
Order By: Relevance
“…Moreover, in many molecular diagnostic laboratories, RNA testing is not part of the routine work flow. Although DNA-based analysis would be easier to implement in most laboratories, accurate METexon14del detection has proven to be challenging on DNA level [22,23]. These mutations are variable in size and position, and can include large intron-exon bordering deletions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in many molecular diagnostic laboratories, RNA testing is not part of the routine work flow. Although DNA-based analysis would be easier to implement in most laboratories, accurate METexon14del detection has proven to be challenging on DNA level [22,23]. These mutations are variable in size and position, and can include large intron-exon bordering deletions.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available amplicon-based NGS panels for DNA analysis display severe limitations in accuracy, detecting no more than 63 % of literature-reported cases of alterations in MET exon 14 due to their design [24]. Davies et al confirmed that 60 % of the samples positive for METex14del by their RNA-based assay were negative in their DNA-based assay, using one of the commercially available panels described in Poirot et al [23]. The panel that was used (Illumina Trusight tumor 26 assay) detects up to 99 % of donor splice site and Y1003 mutations, but only 8 % of acceptor splice site or branch site mutations, according to in silico analysis performed by Poirot et al Indeed, all 11 MET mutations detected by the DNA assay of Davies et al concerned donor splice site mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Through the RNA-seq, MET exon 14 mutation and isocitrate dehydrogenase 1 (IDH1) mutation were identified as new potential therapeutic targets in lung adenocarcinoma and chondrosarcoma patients, respectively [80,81]. Several studies have shown that RNA sequencing can effectively improve the detection rate on the basis of DNA sequencing, provide more comprehensive detection results and achieve a better curative effect for targeted therapy [82]. In addition, it has been proved that IDH mutation is a good prognostic marker for glioma by RNA-seq [83].…”
Section: Differential Gene Expression Analysis and Cancer Biomarkersmentioning
confidence: 99%
“…Testing for these alterations could be included in a broader DNA sequencing panel. However, given the various genomic locations of exon 14 skipping alterations, RNA-based approaches are now being assessed to more comprehensively capture MET exon 14 skipping events in the future [86].…”
Section: Expert Opinionmentioning
confidence: 99%